Selected Bibliography “Attractiveness of vocational education and training : Permeability, successful school-to-work transitions and international mobility" - Linten, Markus [Verfasser]; Prüstel, Sabine [Verfasser]; Woll, Christian [Verfasser]; Roth, Uta [Verfasser]; Wurdak, Alix [Verfasser] (Bundesinstitut für Berufsbildung, 2014)
The bibliography showcases worldwide developments, current innovations and good practices in TVET with the emphasis on attractiveness, permeability, mobility, and transition. This publication reflects the range of currently available literature such as articles, books, government reports, UN agency documents, donor community documents, research theses, and other sources. It contains material that has been published in the last five years. All information included in these reviews was obtained through an extensive search of online journals, conferences, databases and archives. (BIBB-Doku)
Keywords: S System beruflicher Bildung; G 1.3.2.2 Übergänge; G 2.5.3 Anschlussfähigkeit von Bildungsgängen; I 2.3.1 Afrika; I 2.3.2 Nordamerika; I 2.2 Europa; I 2.3.4 Asien; Berufsbildungssystem; Attraktivität; Berufseinmündung; Durchlässigkeit im Bildungssystem; Mobilität; Internationaler Vergleich; Amerika; Afrika; Europa; Asien